An Experimentally Validated Finite Element Model of the Lower Limb to Investigate the Efficacy of Blast Mitigation Systems - Rebelo, Eduardo A.; Grigoriadis, Grigoris; Carpanen, Diagarajen; Bull, Anthony M. J.; Masouros, Spyros D. (Frontiers in Bioengineering and Biotechnology, 2021)
Improvised explosive devices (IEDs) used in the battlefield cause damage to vehicles and their occupants. The injury burden to the casualties is significant. The biofidelity and practicality of current methods for assessing current protection to reduce the injury severity is limited. In this study, a finite-element (FE) model of the leg was developed and validated in relevant blast-loading conditions, and then used to quantify the level of protection offered by a combat boot. An FE model of the leg of a 35 years old male cadaver was developed. The cadaveric leg was tested physically in a seated posture using a traumatic injury simulator and the results used to calibrate the FE model. The calibrated model predicted hindfoot forces that were in good correlation (using the CORrelation and Analysis or CORA tool) with data from force sensors; the average correlation and analysis rating (according to ISO18571) was 0.842. The boundary conditions of the FE model were then changed to replicate pendulum tests conducted in previous studies which impacted the leg at velocities between 4 and 6.7 m/s. The FE model results of foot compression and peak force at the proximal tibia were within the experimental corridors reported in the studies. A combat boot was then incorporated into the validated computational model. Simulations were run across a range of blast-related loading conditions. The predicted proximal tibia forces and associated risk of injury indicated that the combat boot reduced the injury severity for low severity loading cases with higher times to peak velocity. The reduction in injury risk varied between 6 and 37% for calcaneal minor injuries, and 1 and 54% for calcaneal major injuries. No injury-risk reduction was found for high severity loading cases. The validated FE model of the leg developed here was able to quantify the protection offered by a combat boot to vehicle occupants across a range of blast-related loading conditions. It can now be used as a design and as an assessment tool to quantify the level of blast protection offered by other mitigation technologies.